International Economics - Torelli, Paul (Business Expert Press, 2013)
Ebook from IG Library ; Today's news media displays an intense fascination with the global economy--and for good reason. The degree of worldwide economic integration is unprecedented, and rising globalization has lifted living standards and reduced poverty. Foreign markets and new technologies continue to present opportunities for entrepreneurs and corporations. Still, economic shocks can spread across the world in minutes, impacting billions of lives. This book will help you learn about economics in everyday language, using little or no math, giving you better tools to interpret current events as well as long-term economic and political developments. Modern economics offers a powerful framework for understanding globalization, international trade, and economic growth. You may possess years of hands-on experience dealing with business cycles and foreign competitive pressures, but lack a solid grounding in economic concepts that shed light on the forces of globalization. This book is here to help.